Identification of the molecular sex-differentiation period in the siberian sturgeon - Vizziano-Cantonnet, Denise; Di Landro, Santiago; Lasalle, André; Martínez, Anabel; Mazzoni, Talita Sarah [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Wiley-Blackwell, 2015)
Sexual development prior to gonadal sex differentiation is regulated by various molecular mechanisms. In fish, a molecular sex-differentiation period has been identified in species for which sex can be ascertained prior to gonadal sex differentiation. The present study was designed to identify such a period in a species for which no genetic sex markers or monosex populations are available. Siberian sturgeons undergo a slow sex-differentiation process over several months, so gonad morphology and gene expression was tracked in fish from ages 3-27 months to identify the sex-differentiation period. The genes amh, sox9, and dmrt1 were selected as male gonad markers; cyp19a1a and foxl2a as female gonad markers; and cyp17a1 and ar as markers of steroid synthesis and steroid receptivity. Sex differentiation occurred at 8 months, and was preceded by a molecular sex-differentiation period at 3-4 months, at which time all of the genes except ar showed clear expression peaks. amh and sox9 expression seemed to be involved in male sexual development whereas dmrt1, a gene involved in testis development in metazoans, unexpectedly showed a pattern similar to those of the genes known to be involved in female gonadal sex differentiation (cyp19a1 and foxl2a). In conclusion, the timing of and gene candidates involved with molecular sex differentiation in the Siberian sturgeon were identified. Mol. Reprod. Dev. 2015. © 2015 Wiley Periodicals, Inc.